Mudanças teórico-metodológicas no campo da alfabetização sob a perspectiva de professores alfabetizadores - Nacari, Déborah Provetti Scardini (2016)
This research, with historical approach in the 1990s, questions how the process of theoretical and methodological changes was handled among literacy teachers who worked in public schools in the city of Vitória / ES. As such, it takes on a literacy perspective different from the constructivist perspective, as well as the way of thinking and leading the processes of training literacy teachers. While for Emilian constructivist perspective there is a belief that children learn by themselves, spontaneously, through interactions that make the teacher’s role almost invisible (GONTIJO; SCHWARTZ, 2010), we understand literacy as an immersion process of the child in the world of written language (GONTIJO, 2002). Thus, we understand that for children "[...] to take ownership of knowledge and, in particular, the written language, it is required a qualified mediation of teachers [...]" (GONTIJO; SCHWARTZ, 2010, p. 11). In this sense, this understanding builds on the historic-cultural theoretical and methodological perspective, based on studies of Bakhtin and his circle, to think about the language in the literacy process. As we recalled it, we had the opportunity to revisit the implementation of the Single Block, now from the perspective of these literacy teachers. Through their reports, we can infer that the school organization combining the first and second grades, and the constructivism (adopted by the public school system in Vitória, called Single Block) failed to overcome the serious problems of literacy in the first two grades of basic education. It is essential to consider this educational reform as part of the history of education / literacy in the State of Espírito Santo.